2003
DOI: 10.1007/s00359-003-0434-y
|View full text |Cite
|
Sign up to set email alerts
|

(?)-Germacrene D receptor neurones in three species of heliothine moths: structure-activity relationships

Abstract: Specificity of olfactory receptor neurones plays an important role in food and host preferences of a species, and may have become conserved or changed in the evolution of polyphagy and oligophagy. We have identified a major type of plant odour receptor neurones responding to the sesquiterpene germacrene D in three species of heliothine moths, the polyphagous Heliothis virescens and Helicoverpa armigera and the oligophagous Helicoverpa assulta. The neurones respond with high sensitivity and selectivity to (-)-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 14 publications
0
50
0
Order By: Relevance
“…Recently, tetramethylrhodamine dextran was used successfully for staining ORNs of single sensilla (Stranden et al, 2003). It seems that the dextran, coupled to biotin in our case, is crucial for transport to the axon terminals of the ORNs.…”
Section: Selective Staining Of Ornsmentioning
confidence: 99%
“…Recently, tetramethylrhodamine dextran was used successfully for staining ORNs of single sensilla (Stranden et al, 2003). It seems that the dextran, coupled to biotin in our case, is crucial for transport to the axon terminals of the ORNs.…”
Section: Selective Staining Of Ornsmentioning
confidence: 99%
“…For example, Stranden et al (2003) demonstrated structural-activity relationships in the electrophysiological responses of three heliothine moths to the sesquiterpene germacrene D. The selective response of these OSNs to germacrene D was defined by the ten-membered ring system, the position of three double bonds and the position of the isopropyl group. Research on pheromone receptors of the moth Agrotis segetum has also shown that changes in shape and bulkiness, length, position of the double bond or nature of the functional group of the (Z)-5-decenyl acetate molecule (one of the three pheromone components of this species), have an effect, direct or indirect, on the interaction of the molecules with the receptor binding sites.…”
Section: Cpomor19 and Slitor19 Are Tuned To 1-indanonesmentioning
confidence: 99%
“…With a few exceptions (Wibe et al, 1998;Stranden et al, 2002Stranden et al, , 2003, however, little is known about the enantiospecificity of ORCs responding to nonpheromonal odor compounds. To our knowledge, no study in vertebrates or invertebrates has used intracellular recording to examine the enantioselectivity of PNs innervating identified glomeruli.…”
Section: Introductionmentioning
confidence: 99%